UTILIZATION OF BIG DATA IN IMPROVING MARKETING STRATEGIES - Fajriah, Riri (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2024)
Big Data is data characterized by very large, very varied, fast-growing of data and may not need to be treated specially structured with innovative technology to obtain in-depth information and can help in making a better decision. The important things of Big Data is not just about technical capability to process data, but the benefits of its that can be realized by the company by using Big Data Analytics Terminology and it is believed come from web search company which process data the aggregation of distributed very large and unstructured. The challenge of Big Data includes the acquisition, accuracy of data, storage, search (search), the distribution, transfer, data analysis, and data visualization. The trend of Big Data is increasingly enlarged set of data caused by the increase of information from large sets of inter-related, compared with other small associations with the total number of the same data. One of the utilization of Big Data is a boost in sales with improved marketing strategy in matters such as: product campaigns, consumer segmentation and markets analysis, location-based marketing, sentiment analysis, personalized marketing and lure customers.